2006
DOI: 10.1182/blood-2005-09-3826
|View full text |Cite
|
Sign up to set email alerts
|

Relation between JAK2 (V617F) mutation status, granulocyte activation, and constitutive mobilization of CD34+ cells into peripheral blood in myeloproliferative disorders

Abstract: We studied the relationship between granulocyte JAK2 (V617F) mutation status, circulating CD34 ؉ cells, and granulocyte activation in myeloproliferative disorders. Quantitative allele-specific polymerase chain reaction (PCR) showed significant differences between various disorders with respect to either the proportion of positive patients (53%-100%) or that of mutant alleles, which overall ranged from 1% to 100%. In polycythemia vera, JAK2 (V617F) was detected in 23 of 25 subjects at diagnosis and in 16 of 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
246
0
13

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 234 publications
(275 citation statements)
references
References 36 publications
16
246
0
13
Order By: Relevance
“…Indeed, PB from MPN patients has previously been demonstrated to contain an increased CD34 ϩ fraction compared with normal PB. 17 In contrast to PV and ET, the alterations in the size of the HSC and GMP population and the stable allele burden in JAK2 V617F-positive MF suggest an alteration in the regulation of the HSPC compartment through additional mechanisms, such as the presence of other mutations, microenvironment effects, and/or genetic modifiers. These findings are also in consonance with functional differences between human PV and MF V617F mutant HSCs as detected in xenotransplant experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, PB from MPN patients has previously been demonstrated to contain an increased CD34 ϩ fraction compared with normal PB. 17 In contrast to PV and ET, the alterations in the size of the HSC and GMP population and the stable allele burden in JAK2 V617F-positive MF suggest an alteration in the regulation of the HSPC compartment through additional mechanisms, such as the presence of other mutations, microenvironment effects, and/or genetic modifiers. These findings are also in consonance with functional differences between human PV and MF V617F mutant HSCs as detected in xenotransplant experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the percentage of the circulating mutated JAK2 allele was shown to be significantly higher in PV and ET patients who developed myelofibrosis, and may also be significantly higher in patients who develop vascular complications. 90,91 Some authors suggested that IFN-a could delay myelofibrosis development in PV patients 42 based on in vitro data, a benefit that could be mediated by reduction of the proportion of JAK2V617F mutated cells. In addition, the selective effect of IFN-a on mutated granulocytes may affect the incidence of thrombosis, as it has been shown that leukocyte SPOTLIGHT activation and hemostatic changes were correlated with the presence of JAK2 mutation.…”
Section: Ifn-a and Leukemic Evolutionmentioning
confidence: 99%
“…104 The release of CD34( þ ) cells is generally due to a combination of increased levels of proteases 105 and especially due to the downregulation of the CXCR4 receptor on CD34( þ ) cells. 106 An altered SDF-1/CXCR4 axis was demonstrated in PMF patients with CD34( þ ) cells in the periphery.…”
Section: Spotlightmentioning
confidence: 99%